Isotope (δ13C, δ15N, δ2H) diet–tissue discrimination in African grey parrot Psittacus erithacus: implications for forensic studies. Issue 6 (2nd November 2017) - Symes, Craig; Skhosana, Felix; Butler, Mike; Gardner, Brett; Woodborne, Stephan
ABSTRACT: Diet–tissue isotopic relationships established under controlled conditions are informative for determining the dietary sources and geographic provenance of organisms. We analysed δ 13 C, δ 15 N, and non-exchangeable δ 2 H values of captive African grey parrot Psittacus erithacus feathers grown on a fixed mixed-diet and borehole water. Diet–feather Δ 13 C and Δ 15 N discrimination values were +3.8 ± 0.3 ‰ and +6.3 ± 0.7 ‰ respectively; significantly greater than expected. Non-exchangeable δ 2 H feather values (−62.4 ± 6.4 ‰) were more negative than water (−26.1 ± 2.5 ‰) offered during feather growth . There was no positive relationship between the δ 13 C and δ 15 N values of the samples along each feather with the associated samples of food offered, or the feather non-exchangeable hydrogen isotope values with δ 2 H values of water, emphasising the complex processes involved in carbohydrate, protein, and income water routing to feather growth. Understanding the isotopic relationship between diet and feathers may provide greater clarity in the use of stable isotopes in feathers as a tool in determining origins of captive and wild-caught African grey parrots, a species that is widespread in aviculture and faces significant threats to wild populations. We suggest that these isotopic results, determined even in controlled laboratory conditions, be used with caution.